Penelitian Evaluatif dalam Pendidikan - Yuniarti, Yuniarti; Abdiyah, Lathifah; Nurjanah, Siti; Siregar, Septi Lastri; Riani, Puput (YASIN, 2021)
Basically, evaluative research is part of applied research. An important part of evaluative research is the existence of an expected goal or condition, then these goals are assessed through evaluation. Evaluative research is a study that measures and determines the results of a particular plan or project by collecting and analyzing plans objectively, in accordance with the objectives of the plan. The aim is to design, refine and test the implementation of educational practices, as well as evaluate the success of certain activities and evaluate the benefits of these activities. Evaluation will be carried out well if the program includes clear objectives, so that it can determine the expected or achieved results through the methodology of the conceptual framework of research evaluation. There are several evaluation models that can be chosen by researchers to evaluate the program, namely the CIPP, UCLA, Brinkerhoff and Stake models.